2011
DOI: 10.1016/j.jtcvs.2010.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve analysis of mitral valve repair using telemanipulative technology

Abstract: Learning in mitral valve repair surgery using telemanipulative technology occurs at the East Carolina Heart Institute according to a logarithmic curve, with a learning percentage of 95%. From our regression output, we can make an approximate prediction of total robot time using an additive model. These metrics can be used by programs for benchmarking to manage the implementation of this new technology, as well as for capacity planning, scheduling, and capital budget analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Use of clips instead of suture for mitral ring implantation was found to have a positive effect on total robotic time. As expected, we also found that with increased surgeon experience, the procedure complexity increased [45].…”
Section: Learning Curvessupporting
confidence: 86%
“…Use of clips instead of suture for mitral ring implantation was found to have a positive effect on total robotic time. As expected, we also found that with increased surgeon experience, the procedure complexity increased [45].…”
Section: Learning Curvessupporting
confidence: 86%
“…The percentage of patients who required mitral valve reoperation during follow-up has been described in detail in previous publications from our institution, with reoperation rates that are within the range of results published for full sternotomy mitral valve surgery. 2,3,13 However, these studies come from high-volume centers with vast experience in MIS-MV surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons at other centers might be reluctant to adopt the minimally invasive approach because of the initial learning curve involved. Although several publications have discussed the learning curve associated with MIS-MV operations, [3][4][5] such publications are expert opinion only with few supportive data.…”
Section: Inimally Invasive Surgery Of the Mitral Valve (Mis-mv)mentioning
confidence: 99%
“…Charland et al [26] investigated LCs for mitral valve repairs using telemanipulation technology and found a statistically significant LC (p < 0.01) and learning percentage of 95% for safe operation using the technology.…”
Section: Valve Implantation/valve Surgerymentioning
confidence: 99%